Certainty, Uncertainty, or Indifference? Examining Variation in the Identity Narratives of Nonreligious Americans. Issue 5 (October 2019) - Frost, Jacqui
Much research in social science concludes that uncertainty surrounding individual beliefs and identities is negative and anxiety-inducing, and that people are continuously searching for certainty. In the context of rising rates of religious disaffiliation in the United States, and the rise of social and political organizations created to promote nonreligious beliefs and values, the nonreligious offer a strategic case to explore the meaning and lived experience of certainty and uncertainty surrounding belief and identity formation. Drawing on an analysis of identity narratives from 50 nonreligious Americans, I find that uncertainty is just as often experienced as positive and motivating as it is isolating or anxiety-inducing, and although certainty-filled beliefs and identities are available for the nonreligious, they are just as often rejected for more uncertain ones. I reveal how some nonreligious individuals fluctuate between different orientations toward certainty and uncertainty regarding their nonreligion, whereas others exhibit more trait-like orientations to certainty and uncertainty. These findings have important implications for understanding how orientations to certainty and uncertainty shape identity and belief development in the modern world.